On an efficient hybrid soft and hard sphere collision integration scheme for DEM. (22nd October 2016) - Buist, K.A.; Seelen, L.J.H.; Deen, N.G.; Padding, J.T.; Kuipers, J.A.M.
Abstract: This paper introduces a novel hybrid collision integration scheme that combines the benefits of the hard-sphere and the soft-sphere methodology. It assumes that the larger part of the collisions are binary and can be solved in one step. The remainder of the collisions involving more than two particles are handled with a classical soft-sphere scheme. Results for a bounding box problem, employing the classical soft-sphere scheme and the hybrid scheme are compared in terms of energy budget conservation. The hybrid scheme is more accurate and more importantly it is roughly one order of magnitude faster. Abstract : Highlights: Novel hybrid collision integration scheme for discrete element methods. Using hard sphere methodology for binary collisions and soft sphere for multibody collisions. Comparison of classical and hybrid methods by monitoring the energy budget of a bounding box problem.